2018
DOI: 10.1016/j.clinthera.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based Monitoring of Clinical Trials: An Integrative Approach

Abstract: These results provide strong evidence that our RBM methodology can significantly improve the clinical oversight process and do so at a lower cost through more intelligent deployment of monitoring resources to the sites that need the most attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
(8 reference statements)
1
21
0
Order By: Relevance
“…The risk-based quality control approach described in this paper is established and adopted by our institution in March 2019, which is aim to promote the e ciency of quality control activities and contribute to the data reliability. Compared with traditional quality control approaches such as regular quality control activities and 100% SDV, we have found that the RBQC is more adaptive and more bene cial in data quality, consistent with the ndings of reported studies [6,10] . From March 2019 to now, we have observed that RBQC resulted in 33.6% fewer signi cant issues per site monitoring, 41.5% fewer signi cant issues per sponsor audit, 25.6% higher mean interval between quality control activities, and 20.1% lower mean time cost per on-the-spot inspection in 9 clinical trials.…”
Section: Discussionsupporting
confidence: 89%
“…The risk-based quality control approach described in this paper is established and adopted by our institution in March 2019, which is aim to promote the e ciency of quality control activities and contribute to the data reliability. Compared with traditional quality control approaches such as regular quality control activities and 100% SDV, we have found that the RBQC is more adaptive and more bene cial in data quality, consistent with the ndings of reported studies [6,10] . From March 2019 to now, we have observed that RBQC resulted in 33.6% fewer signi cant issues per site monitoring, 41.5% fewer signi cant issues per sponsor audit, 25.6% higher mean interval between quality control activities, and 20.1% lower mean time cost per on-the-spot inspection in 9 clinical trials.…”
Section: Discussionsupporting
confidence: 89%
“…Risk-based monitoring is a data-driven approach which can lead to improvement in the efficiency of monitoring while preserving data quality. 19 This approach has been endorsed by the EMA, and is particularly suited to CID trials given their complexity. 9 Trial management support.…”
Section: Recommendation 9 -Approval and Reimbursement Decisionsmentioning
confidence: 99%
“…For visualizations, we used our proprietary D3.js-based 25 library that we originally developed for our Xcellerate Medical Review application. 4 Finally, for identity management and authentication, we used Okta, 26 an OpenID Connect 27 compliant cloud-based identity provider. All connections to the system are strictly required to be secure, incorporating strong Transport Layer Security (TLS) encryption for all traffic to and from the user's browser.…”
Section: Notification Service: a Scheduled Windows Servicementioning
confidence: 99%
“…The investigator portal presented here is part of a broader clinical trial management suite, known as Xcellerate, that uses advanced data integration, analytics, and visualization capabilities to improve patient safety, data quality, and protocol compliance throughout the clinical development process and enable greater transparency and oversight of study conduct and performance. 4 ā€“ 9 Inspired from previous work in discovery, 10 clinical, 11 , 12 and outcomes research, 13 this solution consists of a number of end-user applications connected to a clinical data repository that supports near-real-time acquisition, mapping, and integration of clinical trial data from any germane source, including laboratory test results, the subject matter of the present work. The Xcellerate Investigator Portal leverages the same architectural and web design principles to provide secure online access to laboratory results, manuals, and training materials through an intuitive interface that enhances user adoption, productivity, and collaboration.…”
Section: Introductionmentioning
confidence: 99%